Surgical treatment of pulmonary aspergilloma - Ruiz Júnior, Raul Lopes [UNESP]; Oliveira, Frederico Henrique Sobral de [UNESP]; Piotto, Bruno Luiz Burgos [UNESP]; Muniz, Felipe Antunes e Silva de Souza Lopes [UNESP]; Cataneo, Daniele Cristina [UNESP]; Cataneo, Antonio José Maria [UNESP] (Sociedade Brasileira de Pneumologia e Tisiologia, 2010)
The objective of this study was to analyze the outcome of surgical treatment of pulmonary aspergilloma. To that end, we evaluated 14 adult patients so treated between 1981 and 2009 at the Botucatu School of Medicine University Hospital, in the city of Botucatu, Brazil. Data were collected from the medical records of the patients. Ten patients (71%) presented with simple pulmonary aspergilloma, and 4 (29%) presented with complex pulmonary aspergilloma. Hemoptysis was the most common symptom, and tuberculosis was the most prevalent preexisting lung disease. Two patients (14%) underwent surgery on more than one occasion. There were no intraoperative deaths. Half of the patients developed postoperative complications, prolonged air leak and empyema being the most common.

O objetivo deste estudo foi analisar o resultado do tratamento cirúrgico de aspergiloma pulmonar. Para tanto, foram avaliados 14 pacientes adultos (7 homens e 7 mulheres) e tratados no Hospital Universitário da Faculdade de Medicina de Botucatu, em Botucatu (SP), entre 1981 e 2009. Dados foram coletados dos registros médicos dos pacientes. Dez pacientes (71%) apresentaram aspergiloma pulmonar simples, e 4 (29%) apresentaram aspergiloma pulmonar complexo. O sintoma mais frequente foi hemoptise, e a pneumopatia preexistente mais prevalente foi tuberculose. Dois pacientes (14%) foram submetidos a mais de um procedimento cirúrgico. Não houve mortalidade operatória. Metade dos pacientes apresentou complicações pós-operatórias, sendo fuga aérea prolongada e empiema as mais frequentes.
Tratamento cirúrgico de aspergiloma pulmonar
Keywords: Pulmonary aspergillosis; Tuberculosis, pulmonary; Thoracic surgery; Aspergilose pulmonar; Tuberculose pulmonar; Cirurgia torácica